Observations on the ultrastructure and hydrophobicity of the wings of thirteen Neotropical families of diptera (insecta) with comments on their flight - Sánchez Monge, Gerardo Alcides (2015)
Insects' wings are complex surfaces that have become a new field to study towards the design of flying devices and hydrophobic surfaces. Several orders and families of insects have been analyzed for their hydrophobic properties and the microstructures related. We studied the wings of 13 dipteran families under scanning electron microscopy and used a goniometer to measure the corresponding static contact angle. Common structures as well as distinct features were found in the samples. None of the wings was superhydrophobic; the contact angles raged from 67.9° to 109.9°. Wings' ultrastructure and cuticle elements are associated with these differences, and play a crucial role during flight.